Best Answer

Normally, you would do this by finding a pair of numbers whose product is equal to the product of the first term's coefficient multiplied by the last term, and whose sum is equal to the coefficient of the second term. Those numbers could then be used to break the expression down further. In other words, you are looking for two numbers, we'll call them A and B, in which (A + B) = -4 and AB = 5. Unfortunately, there are no such numbers, so that expression can not be factored.

🙏

🤨

😮

Study guides

☆☆

Q: How do you factor 5x2 - 4x plus 1?

Write your answer...

Submit

Still have questions?

Related questions

(x + 1)(5x - 1)

-5x2+9x-4 -5x2+9x+-4 Factors of -20 that add to equal 9 are -5 and-4 -5x2+5x+4x+-4 -5x(1x+1) + 4x(1+-1x)

5x2 + 3x - 1 does not have rational factors.

It is 4x^2 + 10x - 1

As written, -5x + 9x = 4x 4x - 4 = 4(x - 1) If that's -5x2 + 9x - 4, that factors to -(x - 1)(5x - 4)

4x + 16 + 1 = 4x + 17 which cannot be factorised.

4x(10x + 1)

It is: 4x(1+4)

5x2-46x+9 = (5x-1)(x-9)

(2x-1)(2x-1) = 4x^2 -4x + 1

OK. 4x2 + 4x + 1 = (2x + 1)2

4x2 + 1 + x2 + 3 = 5x2 + 4

4x(4x^2 + 3x + 1)

(4x - 3)(4x - 1)

5x2 + 29x - 6 = (5x - 1)(x + 6).

(5x - 1)(x + 3)

Add 1 to both sides. The answer is (4x + 1)(4x + 1) or (4x + 1)2

I am assuming the question is to factor this problem? 5x2 + 29x - 6 (5x - 1)(x + 6)

(5x + 2)(x + 1)

(4x - 1)(x - 5)

(4x - 3)(x - 1)

-((4x + 1)(x - 1))

x3 + x2 + 4x + 4 = (x2 + 4)(x + 1)

(2x + 1)(4x + 7)

4x2 - 4x + 2xy - 2y = 4x(x - 1) + 2y(x - 1) (4x + 2y)(x - 1).